Design optimization of a mold for producing a complex-geometry blade - Maiorova, Kateryna; Shypul, Olga; Lysochenko, Ihor; Hoptar, Taras; Kapitanova, Liudmyla; Voronko, Iryna (Technology audit and production reserves, 2025)
The object of research is a mold with complex geometry for casting a turbine blade prototype, made by 3D printing from Anycubic photopolymer resin and PETG (Polyethylene Terephthalate Glycol) polymer. Problem to be solved: ensuring the necessary strength and rigidity of the mold during the assembly of half-molds by bolted connection with preliminary axial tension. Using Siemens NX Advanced Simulation, finite element models of the mold were created and calculated. It was found that with significant preliminary axial tension, the limit stresses in the bolt hole area are exceeded, which limits the use of photopolymer resin. Reducing the tightening force improves the performance, but leaves a minimum margin of safety. The rigidity of the mold can be increased by using support pads, but such a design causes stress concentration in the bolted connections. The optimal calculation result was achieved when using PETG material: the safety margin increased to η = 1.5, and the displacements did not exceed 0.04 mm. The PETG polymer, unlike photopolymer resin, is more elastic and plastic in the hardened state with higher strength. This allows to distribute the load over the material. The results obtained can be used for the manufacture of molds for casting and tooling in general, especially for a small batch of parts. The practical application of the technology under consideration is possible provided that the input parameters are correctly combined: material, bolt pre-tightening force and the use of support pads. PETG is recommended for molds operating under increased loads.